(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To determine the correlation of international prostate symptom score with Intravesical protrusion of prostate. Methods: This prospective clinical study was performed on 60 elderly patients presented with LUTS suggestive of Benign Enlargement of Prostate. Their evaluation included DRE, IPSS, Uroflowmetry (Qmax), serum PSA measurements and trans abdominal ultrasound scan. Statistical analysis was performed by SPSS version 13 using Chi square test and scatter plots together with Spearman’s correlation coefficients were used to assess the relationship between IPP and IPSS. Results: Mean age of the patients was 66.7+9.85 years, IPSS 23.6+6.53, mean prostatic volume was 60.23+38.16 mL, Qmax 7.98+3.87, PVR was 163.18+141.73 mL. Fifty percent of patients had severe degree (>10mm) of intravesical protrusion of the prostate, 30% had moderate and 20% had mild IPP. There was significant positive correlation between IPSS and IPP (r=0.698, P < 0.001). Conclusion: From this prospective clinical study it is revealed that IPP had strong correlation with IPSS. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.151-154